Iii. Tories, Catholics, and the General Election of 1859 - Hoppen, K. Theodore (The historical journal, 1970)
The fine and delicate balance of political forces and interests in midnineteenth century Britain is nowhere better demonstrated than in the activities of certain social and religious pressure groups during the general election campaign of 1859. The two main parties were certainly conscious of their past and of the traditions imposed upon them by those who had gone before; equally certainly the differences between them were more the outcome of these traditions than of real contemporary disagreements as to policy or outlook. The Tory administration led by Lord Derby, which had come to power in February 1858, was in a minority in the House of Commons. Its survival depended on an ability to attract dissident Whigs and men of independent views. Derby, never the most optimistic of men, had realized as early as April 1857 that his party, ‘if not an actual corpse’, was at most ‘in a state of suspended animation’.1 By the beginning of 1859 it had become evident to a number of Tory leaders, and particularly to Disraeli, that if thegovernment were to survive, it would be necessary to obtain help from quarters hitherto untapped by the party. A peculiar set of circumstances led Disraeli to look to sections of the Roman Catholic community for such support. Although Catholicism was a growing force in England, the centre of its political operations lay of course in Ireland, which then returned 105 members to Westminster.